2015
DOI: 10.1093/nar/gkv1022
|View full text |Cite
|
Sign up to set email alerts
|

Epitope-tagged yeast strains reveal promoter driven changes to 3′-end formation and convergent antisense-transcription from common 3′ UTRs

Abstract: Epitope-tagging by homologous recombination is ubiquitously used to study gene expression, protein localization and function in yeast. This is generally thought to insulate the regulation of gene expression to that mediated by the promoter and coding regions because native 3′ UTR are replaced. Here we show that the 3′ UTRs, CYC1 and ADH1, contain cryptic promoters that generate abundant convergent antisense-transcription in Saccharomyces cerevisiae. Moreover we show that aberrant, truncating 3′ –end formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…At the same time, we note that the strategy of Hurst et al was a heuristic that tried to make the best use of the data already available and did not attempt to model many intricacies, including the cell specificity of ChIP-seq peaks [33], antisense transcription [34,35], temporal dynamics during development [36], long-range promoter-enhancer associations [16], and the existence of chromosomal domains and nuclear subcompartments [37,38]. To model these intricacies would be much more challenging and most likely not possible without new data being generated.…”
Section: Lessons From Mammalsmentioning
confidence: 99%
“…At the same time, we note that the strategy of Hurst et al was a heuristic that tried to make the best use of the data already available and did not attempt to model many intricacies, including the cell specificity of ChIP-seq peaks [33], antisense transcription [34,35], temporal dynamics during development [36], long-range promoter-enhancer associations [16], and the existence of chromosomal domains and nuclear subcompartments [37,38]. To model these intricacies would be much more challenging and most likely not possible without new data being generated.…”
Section: Lessons From Mammalsmentioning
confidence: 99%
“…After overnight growth, the cell culture was then spread on a 5-FOA plate to select for cells that produce the full-length GFP fusion of the protein of interest ( Fig 1C ). Unlike C-terminal gene tagging with a marker, the scarless C-terminal tagging method does not disrupt the endogenous 3’ UTR, which can be important for mRNA localization [ 13 16 , 42 ] and regulation of transcription [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sequences in the 3’ UTR can also control the endogenous sub-cellular localization of the mRNA, which is often coupled to the localization and expression of the protein [ 13 16 ]. In addition, it was recently shown that the widely used CYC1 and ADH1 3’ UTRs contain cryptic promoters that lead to abundant convergent antisense transcription, which may also interfere with normal protein expression [ 17 ]. Any changes to the UTRs that may affect protein abundances are of concern, especially for quantitative studies that measure protein levels [ 3 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have previously shown that the use of distal polyadenylation sites is linked to upregulation of transcriptional initiation ( Swaminathan and Beilharz, 2016 ) and elongation rate ( Pinto et al, 2011 ). To test the idea that a change in nucleotide metabolism caused by cordycepin treatment leads to an increase in transcription rate and thus use of distal poly(A) sites, 4-thiouracil (4tU) labelling was used.…”
Section: Resultsmentioning
confidence: 99%